Opportunist Coinfections by Nontuberculous Mycobacteria and Fungi in Immunocompromised Patients - Ines Joao; Helena Bujdáková; Luisa Jordao (MDPI AG, 2020)
Nontuberculous mycobacteria (NTM) and many fungal species (spp.) are commonly associated with opportunistic infections (OPIs) in immunocompromised individuals. Moreover, occurrence of concomitant infection by NTM (mainly spp. of Mycobacterium avium complex and Mycobacterium abscessus complex) and fungal spp. (mainly, Aspergillus fumigatus, Histoplasma capsulatum and Cryptococcus neoformans) is very challenging and is associated with poor patient prognosis. The most frequent clinical symptoms for coinfection and infection by single agents (fungi or NTM) are similar. For this reason, the accurate identification of the aetiological agent(s) is crucial to select the best treatment approach. Despite the significance of this topic it has not been sufficiently addressed in the literature. This review aims at summarizing case reports and studies on NTM and fungi coinfection during the last 20 years. In addition, it briefly characterizes OPIs and coinfection, describes key features of opportunistic pathogens (e.g., NTM and fungi) and human host predisposing conditions to OPIs onset and outcome. The review could interest a wide spectrum of audiences, including medical doctors and scientists, to improve awareness of these infections, leading to early identification in clinical settings and increasing research in the field. Improved diagnosis and availability of therapeutic options might contribute to improve the prognosis of patients' survival.